Efisiensi Alokasi Bahan Baku dan Tenaga Kerja Langsung untuk Mengurangi Biaya Produksi - Tulipa, Diyah (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2004)
Technological implementation of manufacture is not focused on its technical problems but exactly on managerial problems. Planning is needed to minimize risk. In order to minimize risk the effort be conducted with efficiency of production factors, Raw material and direct labor are two of production factors that involved directly to production process. Most industries face that raw is the biggest expense component. Direct labor can not reduce production cost directly. It has to optimalize in aim to increase productivity. Efficiency of allocation of raw material and direct labor improve the productivity. Than, the company has provides competitive advantages.